ANALISIS HISTORIS DAN KELEMBAGAAN DINAMIKA SISTEM PENDIDIKAN PONDOK PESANTREN AL-FALAH BANJARBARU: REFLEKSI SETENGAH ABAD (1975–2025) - Muhamad Ramli (Program Studi PAI STAI Al Falah Banjarbaru, 2026)
This research aims to describe in depth the historical journey and institutional evolution of Pondok Pesantren Al Falah Banjarbaru over a span of 50 years (1975–2025). The main focus of this study is to explore the dynamics of the educational system, curriculum transformation, and the development of infrastructure that supports the institution's sustainability. This study employs a qualitative approach with a descriptive-analytical method. Primary data were sourced from internal organizational documents and historical records of its founding, while secondary data were obtained from supporting literature such as the founder's biography and previous research reports. Data collection techniques were conducted through documentation studies, observations, and supporting interviews. The results indicate that Pondok Pesantren Al Falah has transformed from a simple concept in 1975 into a prominent Islamic educational institution that has successfully integrated a